FENOMENA KEDUDUKAN HUKUM ANAK ZINA - Tutut Sartika Siregar; Khairil Anwar (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
Marriage in Islam has noble purposes and wisdom, including creating peace of mind for husband and wife, personal maturity for both, and the birth of a quality generation. Discussions on marriage in the millennial era often encounter new problems, such as the emergence of the term